Tissue-Culture Propagation of the Cactus Echinopsis Turbinata L. - Holder, P L; Kirkham, M B (Annals of Arid Zone, 2016)
Plants of Echinopsis turbinata L. (Cactaceae) were obtained by propagating the cactus with tissue cultures. The basal medium was that of Murashige and Skoog, supplemented with kinetin (0 to 6.5 mg/l), naphthalene-I-acetic acid (0 to 1.4 mg/l), and 2, 4-dichlorophenoxyacetic acid (0 or 1.1 mg/l). Shoots grew before roots. Shoots developed within four to five weeks and root within six to nine weeks. Each mother-plant of the cactus had a potential of producing about 65 plants. The results suggested that, using tissue culture, large numbers of cactuses could be propagated for biomass production in desert regions.